HIF-1α-induced miR-23a∼27a∼24 cluster promotes colorectal cancer progression via reprogramming metabolism. (January 2019) - Jin, Fangfang; Yang, Rong; Wei, Yao; Wang, Dong; Zhu, Yanan; Wang, Xiaohua; Lu, Yousheng; Wang, Yanbo; Zen, Ke; Li, Limin
Abstract: Tumor cells switch metabolic profile from oxidative phosphorylation to glycolysis in a hypoxic environment for survival and proliferation. The mechanisms governing this metabolic switch, however, remain incompletely understood. Here, we show that three miRNAs in the miR-23a∼27a∼24 cluster, miR-23a, miR-27a and miR-24, are the most upregulated miRNA cluster in colorectal cancer (CRC) under hypoxia. Gain- and loss-of-function assays, a human glucose metabolism array and gene pathway analyses confirm that HIF-1α-induced miR-23a∼27a∼24 cluster collectively regulate glucose metabolic network through regulating various metabolic pathways and targeting multiple tricarboxylic acid cycle (TCA)-related genes. In specific, miR-24/VHL/HIF-1α in CRC form a double-negative feedback loop, which in turn, promotes the cellular transition to the 'high HIF-1α/miR-24 and low VHL' state and facilitates cell survival. Our findings reveal that the miR-23a∼27a∼24 cluster is critical regulator switching CRC metabolism from oxidative phosphorylation to glycolysis, and controlling their expression can suppress colorectal cancer progression. Highlights: HIF-1α induced miR-23a∼27a∼24 cluster expression on transcriptional level. miR-23a∼27a∼24 cluster collectively reprogram cancer metabolism from TCA to glycolysis via various metabolic pathways. miR-24/VHL/HIF-1α form a double-negative feedback loop, more favorable for cancer cell survival and tumor progression.